Developing person‐centred care competencies for the healthcare workforce to support family caregivers: Caregiver centred care. (19th September 2020) - Parmar, Jasneet; Anderson, Sharon; Duggleby, Wendy; Holroyd‐Leduc, Jayna; Pollard, Cheryl; Brémault‐Phillips, Suzette
Abstract: Family caregivers (FCGs) are an integral part of the healthcare system. Currently, FCGs provide 70%–90% of the care required by community‐dwelling children and adults living with complex chronic conditions and frailty. Despite FCG's contributions and the growing proportion of distressed caregivers, support for FCGs has not been a health system priority. Researchers have proposed training to enhance the competencies of health providers to work effectively with FCGs. In the absence of best practices for the competency indicators for caregiver‐centred care, we have developed a competency framework for training the health workforce to support FCGs. The objectives in this paper are fourfold: (a) a brief review of stakeholder engagement that led to the development of the competencies the health workforce needs to support FCGs, (b) a description of the process used to name the competency domains, (c) a report on the Modified Delphi process (conducted 2019) used to validate the domain indicators, and (d) a description of the competency framework. We adopted a caregiver and a multilevel interdisciplinary stakeholder codesign approach throughout the competency development process. The competency domains include: (a) Recognising the Caregiver Role, (b) Communicating with FCGs, (c) Partnering with FCGs, (d) Fostering Resilience in FCGs, (e) Navigating Health and Social Systems and Accessing Resources, and, (f) Enhancing the Culture and Context of Healthcare. Our Caregiver‐Centred Care Competencies for the health workforce are only a first step in supporting FCGs in their vital roles. There are few education and training resources to enable and empower health providers to support FCGs, there is an urgent need to develop training resources for the health workforce to recognise and support FCGs.